Co-operative Effect Between γ-Aminobutyric Acid A Receptors and Central-Type Benzodiazepine Receptors on Amylase Release in Rat Parotid Acinar Cells - Migiwa Okubo; Mitsuru Kawaguchi (Elsevier, 2010)
We investigated the inhibitory role of γ-aminobutyric acid A (GABA A ) receptors on amylase release and the evidence for functional coupling with central-type benzodiazepine receptors in rat parotid acinar cells. Muscimol and GABA decreased isoprenaline-induced amylase release. This effect was blocked by bicuculline, a GABA A-receptor antagonist, and enhanced by clonazepam, a central-type benzodiazepine-receptor agonist, and diazepam, a central- and peripheral-type benzodiazepine-receptor agonist. Although bicuculline completely blocked the combination effect of GABA A-receptor agonist and clonazepam, it did not completely block the combination effect with diazepam. These results suggest that protein secretion is suppressively regulated by GABA A receptors coupled with central-type benzodiazepine receptors. Keywords:: γ-aminobutyric acid A receptor, parotid gland, amylase release